2010
DOI: 10.1159/000316761
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Stereotactic Accuracy of the Cosman-Robert-Wells Frame and Nexframe Frameless Systems in Deep Brain Stimulation Surgery

Abstract: Introduction: The primary goal of stereotactic systems in deep brain stimulation (DBS) surgery is accurate delivery of a DBS lead to a target identified on imaging. Thus, it is critical to understand the accuracy of the stereotactic systems and the factors which may be associated with a decrease in accuracy. Methods: Ninety patients underwent microelectrode recording-guided placement of 139 DBS leads by a single surgeon using the Cosman-Roberts-Wells (CRW) frame (n = 70) or a frameless skull-mounted trajectory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 45 publications
3
35
0
Order By: Relevance
“…They only reported absolute errors due to the small number of evaluated lead placements (10 placed leads with Nexframe). Our results in euclidean errors are in line with the results of Holloway et al [10] and Kelman et al [9], with 2.71 mm for Nexframe and 2.63 mm for the Leksell frame. With a Nexframe sample size of 78 placed leads, our study is the largest reported for this ‘frameless' method and the only large study directly comparing Nexframe with the Leksell frame.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…They only reported absolute errors due to the small number of evaluated lead placements (10 placed leads with Nexframe). Our results in euclidean errors are in line with the results of Holloway et al [10] and Kelman et al [9], with 2.71 mm for Nexframe and 2.63 mm for the Leksell frame. With a Nexframe sample size of 78 placed leads, our study is the largest reported for this ‘frameless' method and the only large study directly comparing Nexframe with the Leksell frame.…”
Section: Discussionsupporting
confidence: 93%
“…Bjartmarz and Rehncrona [13] reported a superior accuracy of the Leksell frame with 1.2-mm (Leksell) and 2.5-mm (Nexframe) euclidean errors; however, the sample size was small, with 13 placed leads in both groups. Kelman et al [9] compared Nexframe to the Cosman-Roberts-Wells (CRW) frame and found no significant difference in euclidean errors for both techniques. They reported a 2.65-mm (CRW) euclidean error with 70 leads and a 2.78-mm (Nexframe) euclidean error with 69 placed leads.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, the STN target cannot always be well identified on the preoperative image [10,11,12]. Secondly, the clinical application accuracy of the various stereotactic systems is 0.1–5.0 mm [13,14,15,16,17,18], an error which approaches the dimension of the STN itself. Image fusion inaccuracies, MRI distortion and intraoperative brain shift may add to this error [19,20].…”
Section: Introductionmentioning
confidence: 99%